Persepsi Kayawan Atas Faktor Pembentuk Kepemimpinan Transformasional Pada BMT Tamzis Bandung - Mugi Juwita; Aan Hardiyana (Majalah Bisnis & IPTEK, 2018)
Studies of leadership are currently dominated by transformational leadership, which based on transformational leadership research can make the organization run effectively. Transformational leadership has several dimensions that shape it. This study aims to determine what dimensions are the dominant dimensions in transformational leadership. The survey research approach was carried out on employees at the Baitul Maal WaTamwil Tamzis in Bandung. The test is based on the perception of employees of Baitul Maal Wa Tamwil Tamzis in Bandung as many as 37 people. The data analysis technique used PLS SEM with Smart PLS 3 for tools. The results showed that it was proven that the four dimensions were transformational leadership factors where the motivation dimension was the dominant factor in transformational leadership in Baitul Maal Wa Tamwil Tamzis in Bandung. With the results of these studies, managerial parties in Baitul Maal Wa Tamwil Tamzis in Bandungneed to increase Motivation of Inspiration so that transformational leadership can run optimally.